Cannabidiol inhibits THC-elicited paranoid symptoms and hippocampal-dependent memory impairment. (January 2013) - Englund, Amir; Morrison, Paul D; Nottage, Judith; Hague, Dominic; Kane, Fergus; Bonaccorso, Stefania; Stone, James M; Reichenberg, Avi; Brenneisen, Rudolf; Holt, David; Feilding, Amanda; Walker, Lucy; et al.
Community-based studies suggest that cannabis products that are high in Δ 9 -tetrahydrocannabinol (THC) but low in cannabidiol (CBD) are particularly hazardous for mental health. Laboratory-based studies are ideal for clarifying this issue because THC and CBD can be administered in pure form, under controlled conditions. In a between-subjects design, we tested the hypothesis that pre-treatment with CBD inhibited THC-elicited psychosis and cognitive impairment. Healthy participants were randomised to receive oral CBD 600mg ( n =22) or placebo ( n =26), 210 min ahead of intravenous (IV) THC (1.5 mg). Post-THC, there were lower PANSS positive scores in the CBD group, but this did not reach statistical significance. However, clinically significant positive psychotic symptoms (defined a priori as increases ≥3 points) were less likely in the CBD group compared with the placebo group, odds ratio (OR)=0.22 (χ 2 =4.74, p <0.05). In agreement, post-THC paranoia, as rated with the State Social Paranoia Scale (SSPS), was less in the CBD group compared with the placebo group ( t =2.28, p <0.05). Episodic memory, indexed by scores on the Hopkins Verbal Learning Task-revised (HVLT-R), was poorer, relative to baseline, in the placebo pre-treated group (-10.6±18.9%) compared with the CBD group (-0.4%±9.7 %) ( t =2.39, p <0.05). These findings support the idea that high-THC/low-CBD cannabis products are associated with increased risks for mental health.